On Soft gr-Closed sets in Soft Topological Spaces - V, Jeyanthi.; C, Janaki. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
The aim of this paper is to introduce soft pgr-closed sets in topological spaces which is defined over the universe of the given set with a fixed set of parameters. Further, we investigate its properties and its relationship with other soft closed sets.